HIGH PRECISION MEASUREMENTS OF Mg/Ca AND Sr/Ca RATIOS IN CARBONATES BY COLD PLASMA INDUCTIVELY COUPLED PLASMA QUADRUPOLE MASS SPECTROMETRY - Shen C.-C.; Chiu H.-Y.; Chiang H.-W.; Chu M.-F.; Wei K.-Y.; Lin Y.-S.; Lo L.; Steinke S.; Chen M.-T. (My University, 2007)
We present a new high precision analytical method for the determination of Mg/Ca and Sr/Ca ratios in carbonates using an inductively coupled plasma quadrupole mass spectrometer (ICP-QMS) with a 650-W cold plasma technique and a desolvation introduction system. Signal intensities are detected in pulse-counting mode and Mg/Ca and Sr/Ca ratios are calculated directly from intensity ratios of 24Mg/43Ca and 86Sr/43Ca using external matrix-matched standards for every 4-5 samples to correct for instrumental mass discrimination and low-frequency ratio drift. Significant matrix effect of Ca content on Mg/Ca determination (- 0.018 Mg/Ca (mmol/mol)/[Ca] (ppm)), can be overcome by diluting [Ca] to 6-8 ppm in the sample solution or using an empirical correction. The Sr/Ca ratio affects the Mg/Ca determination, with a factor of - 0.32% Mg/Ca per mmol/mol. This is mainly caused by the influence of doubly charged 86Sr, which biases the intensity measurement of the 43Ca+ ion beam. This effect results in a trivial offset of less than 0.1% on Mg/Ca measurements for Quaternary foraminiferal and coral samples. The internal precision of our method ranges from 0.1 to 0.2%. Replicate measurements made on standards and samples show long-term external uncertainties (2σ) of Mg/Ca = 0.84% and Sr/Ca = 0.49%. The minimum sample size requirement is only 3.5 μg of carbonate. The application of this newly developed technique on the planktonic foraminifera Globigerinoides ruber from a core recovered in the southern South China Sea yields a glacial-interglacial difference in sea surface temperature (SST) of 3 °C. Three-year coral Sr/Ca data suggest that the seasonal SST ranged from 22.6-23.8 °C in winter to 26.9-27.9 °C in summer in Nanwan, south Taiwan, during 2000-2002. The coral-Sr/Ca inferred SSTs in 2002 match well with instrumental records, which demonstrates the validity of this ICP-QMS method. © 2006 Elsevier B.V. All rights reserved.
Keywords: CARBONATE; COLD ICP-QMS; CORAL; FORAMINIFERA; Mg/Ca; Sr/Ca; Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная